Integration of Ethnopharmacology and One Health Approach for Rabies Control in Kualin, East Nusa Province - Muntasir, Muntasir; Dean, Muhajirin; Regaletha, Tadeus Andreas Lada; Nabuasa, Bernadeta Stien Julian; Lenggu, Chatrin Jansye; Oematan, Videl Apsi (International Journal of Engineering, Science and Information Technology, 2025)
The ethnopharmacological approach and One Health framework offer a novel perspective with significant potential in controlling rabies cases in East Nusa (NTT), Indonesia. Traditional medicines rooted in local knowledge can complement existing prevention and treatment strategies. This descriptive study involved 20 respondents to explore local practices related to rabies treatment. The findings indicate that integrating ethnopharmacological insights with the One Health approach can contribute significantly to rabies control, particularly in Kualin Subdistrict, South Central Timor Regency, NTT. The study identified local practices, analyzed their integration with modern medical interventions, and educated the community about rabies prevention. These results highlight the importance of incorporating ethnopharmacological knowledge into public health programs while promoting cross-sectoral collaboration in human, animal, and environmental Health. Further research is needed to evaluate the efficacy of medicinal plants used by the community. Additionally, developing community-based educational programs and strengthening collaborations between the government, non-governmental organizations, and local communities are crucial for creating effective and sustainable strategies for rabies control in NTT.